Rural library – center for culture and social support - O. L. Lavrik (Библиосфера, 2019)
Book Review:Kuzoro K. A., Lyapkova A. A., Masyaykina E. A., Degtyareva A. I. Social Work of Rural Libraries in Tomsk Region: Directions, Opportunities, Contribution to Rural Development (2000-2010) / Ed. K.A. Cuzoro. Tomsk: Publishing House Tom. University, 2019.116 p. (In Russ.).